Avaliação do potencial patogênico in vitro de fungos presentes em solos ornitogênicos da Antártica - Jordana Rosa Paiva de Sousa (2016)
The Antarctic continent is characterized by its geographical and climatic isolation, as well as for little or no anthropogenic influence. Considered one extremophile continent, Antarctica presents conditions classified as limiting for animal and plant life. However, the microorganisms stand out because they have various adaptations to the harsh conditions found in the Antarctic environment. Among the microorganisms, fungi are highlighted by its high adaptive capacity to extreme conditions. The distribution of fungi in Antarctica is related to the different substrates/habitats in the area. Antarctic soils are generally oligotrophic; however, there are so-called ornithogenic soils that are rich in organic matter from occupation by birds. The presence of fungi in ornithogenic soils is already known, however, the contact consequences of these soils with the humans have not been questioned. The aim of this study was to verify if in these soils exist fungi that may pose some risk to human health. For this work ornithogenic soils samples were collected at different points in the King George, Livingston and Half Moon Islands which are part of the South Shetland Islands in the Antarctic Peninsula. One g of each soil sample will be inoculated in sterile saline and 100 uL of the dilution 10-1 was be plated on in various culture media, temperatures and pH ranges. After processing samples, were obtained 368 isolates of filamentous fungi and 113 yeasts, which were subjected to growth test at 37 °C. Only those which grew at 37 °C were subjected to further virulence tests in vitro (hemolytic activity, growth in different pH ranges, spores diameter measurement, phospholipase production, capsule and melanin, as well as sensitivity to the antifungal amphotericin B). The 50 thermotolerant fungi were identified as 14 taxa of the genus Aspergillus, Byssochlamys, Chrysosporium, Cryptococcus, Debaryomyces, Eutypella, Penicillium, Peniophora, Phanerochaete, Phlebia, Psathyrella, Rhizopus and Trametes. Between 50 fungal isolates, 29 (58%) grew at 40 ° C; 27 (54%) showed hemolytic activity; 26 produced spores diameter compatible with alveolar deposition and 16 (32%) had phospholipase activity. All isolates grew at pH 7, 45 (90%) grew at pH 4 and 48 (96%) at pH 9. The 12 Cryptococcus laurentii isolates showed capsular polysaccharide and resistance profile of amphotericin B (MIC greater than 1 μg/mL). The results of this study suggest that fungi isolated from environmental samples from Antarctic may have different virulence factors, in vitro, which is a health risk, particularly of immunosuppressed people. In addition, this study supports the hypothesis that the fungal adaptation to extreme environmental conditions such as the Antarctic, may result in the ability of these eukaryotes to infect human hosts, emphasizing the importance of studying extremophiles fungi as potential opportunistic microorganisms.